Large-Scale Segmentation of the Paraguay River Based on Morphological and Hydro-Sedimentary Criteria - Silva, Edson Rodrigo dos Santos da; Silva, Aguinaldo; Macedo, Hudson de Azevedo; Kuerten, Sidney; Luz, Leandro Domingos (Revista Brasileira de Geomorfologia, 2025)
Hydro-geomorphological dynamics in the Pantanal wetlands remain poorly understood, requiring more comprehensive investigations. Geomorphological compartmentalization has been particularly useful in this endeavor, although such approach presents limitations in terms of analytical scale. Here, we proposed the geomorphological segmentation of a reach of Upper Paraguay River, between Porto da Manga and Porto Murtinho (Mato Grosso do Sul, Brazil) as a framework to better understand the hydro-geomorphological processes in the Pantanal wetlands. Our study integrates multiple geomorphological, hydrological, and geological criteria to define six geomorphological segments in the Paraguay River meander belt, named after local toponym, i) Porto Esperança, ii) Forte Coimbra, iii) Bahia Negra, iv) Barranco Branco, v) Fecho dos Morros, and vi) Porto Murtinho. Remote sensing data, digital elevation models (DEMs), and previous geomorphological mappings were combined here through geoprocessing and manual vectorization techniques. The results reveal that fluvial dynamics along the Upper Paraguay River are highly heterogeneous and influenced by structural controls, geomorphological variability, and channel–floodplain interactions. Hydraulic bottlenecks exert a strong influence on flow regulation and discharge redistribution as the abrupt shifts in channel orientation, sinuosity, and meander-belt width reflect the interplay among hydro-sedimentary processes and tectonic lineaments. This segmentation framework enhances our understanding of the Paraguay River morpho-hydrodynamics and provides a valuable contribution for improving environmental and water resources management in the Pantanal basin, home of the world’s largest tropical wetland.